W and Er doped RuO2 catalyst, preparation method and application thereof in acid electro-catalysis water splitting oxygen desorption reaction

The W and Er doped RuO2 catalysts were prepared by hydrothermal synthesis, which solved the problem of difficult regulation of the reaction activity and stability of RuO2 under acidic conditions, and achieved significantly improved OER catalytic performance and long-term stability.

CN119465222APending Publication Date: 2025-02-18JILIN NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411588162.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Under acidic conditions, the reactive activity and long-term stability of RuO2 catalysts are difficult to adjust, limiting their application in electrochemical water decomposition.

Method used

The W and Er doped RuO2 catalyst (W-Er-RuO2) was synthesized by hydrothermal synthesis method, and the electronic structure of metal Ru in the catalyst was adjusted by doping W and Er to improve its OER catalytic performance under acidic conditions.

Benefits of technology

The OER performance of the catalyst is significantly improved. When the current density reaches 10mA cm-2 in 0.5M H2SO4, the overpotential is only 140mV, and the activity can be maintained for more than 130 hours, which is better than commercial RuO2 and IrO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465222A_ABST
    Figure CN119465222A_ABST
Patent Text Reader

Abstract

The invention discloses a W and Er-doped RuO2 catalyst, a preparation method and application of the W and Er-doped RuO2 catalyst in an electrocatalytic water splitting oxygen desorption reaction under an acidic condition, and belongs to the technical field of electrocatalytic water splitting. A transition metal W and rare earth element Er doped RuO2 catalyst is synthesized under a relatively mild condition by adopting a hydrothermal synthesis method, the RuO2 catalyst has the characteristics of high activity and high stability, and the doping of W and Er adjusts the electronic structure of metal Ru in the catalyst, so that the OER catalytic performance of W-Er-RuO2 under an acidic condition is remarkably improved. The catalyst shows excellent OER performance at 0.5 M H2SO4, the overpotential is only 140 mV when the current density reaches 10 mA cm <-2 >, the activity can be maintained for 130 h or above, and the catalytic performance is superior to that of commercial RuO2 and IrO2. Therefore, the RuO2 catalyst which is high in performance and stable in crystal structure is synthesized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalytic water splitting, and specifically relates to a W and Er doped RuO2 catalyst, a preparation method and application thereof in electrocatalytic water splitting oxygen release reaction under acidic conditions. Background Art

[0002] Among many clean energy sources, hydrogen energy is considered to be one of the most promising clean energy sources due to its high energy density and zero carbon emissions. As a zero-carbon emission energy carrier, hydrogen has become a perfect solution to meet the growing energy demand. Among the many hydrogen production technologies, acidic electrochemical water splitting using proton exchange membrane electrolyzer (PEMWE) has greater prospects. The advantages of water electrolysis under acidic conditions are high proton concentration, which can provide higher current density, fast load response and fewer side reactions. In the process of water electrolysis, the oxygen evolution reaction (OER) is kinetically slower than the hydrogen evolution reaction (HER) at the cathode, so the efficiency of electrochemical water splitting is determined by the OER at the anode. Due to the dominant role of OER in water electrolysis, the energy community has been committed to discovering better OER catalysts in recent decades.

[0003] IrO2 is a common acidic OER catalyst in industry, but its high price and low abundance greatly limit its application. In contrast, RuO2 is a promising alternative to IrO2 due to its low cost and relatively high activity. However, regulating the reactivity and long-term stability of RuO2 under acidic conditions remains a major challenge. Summary of the invention

[0004] The present invention aims to improve the utilization rate of energy conversion and the development of hydrogen economy, and proposes a W and Er doped RuO2 catalyst, a preparation method and its application in electrocatalytic water splitting oxygen decomposition reaction under acidic conditions.

[0005] The present invention adopts a hydrothermal synthesis method to synthesize the transition metal W and rare earth element Er doped RuO2 catalyst (W-Er-RuO2) under relatively mild conditions. It has the characteristics of high activity and high stability. The doping of W and Er adjusts the electronic structure of metal Ru in the catalyst, so that the OER catalytic performance of W-Er-RuO2 in acidic conditions is significantly improved. The catalyst shows excellent OER performance in 0.5M H2SO4, and the current density reaches 10mA cm -2 When the overpotential is 140 mV, the activity can be maintained for more than 130 h, and the catalytic performance is better than that of commercial RuO2 and IrO2.

[0006] The preparation method of the W and Er doped RuO2 catalyst described in the present invention comprises the following steps: first, a certain amount of citric acid and ethylenediaminetetraacetic acid (EDTA) are added into deionized water, and the pH value of the solution is adjusted to 7-10 to prepare a solution A; a ruthenium source, an erbium source and a tungsten source are added into the deionized water, and stirred until uniformly dissolved to form a solution B; the solution A and the solution B are uniformly mixed, added into a reaction kettle, and subjected to a hydrothermal reaction at 70-100° C. for 10-15 hours; the obtained reaction solution is centrifuged to obtain a black precipitate, and then the obtained black solid precursor is dried at 50-70° C.; finally, the precipitate is loaded into a corundum boat and transferred to a muffle furnace, and the precipitate is calcined at 280-320° C. for 3-5 hours and at 380-900° C. for 1.5-3.0 hours in an air atmosphere to obtain the W and Er doped RuO2 catalyst.

[0007] Furthermore, the molar ratio of the tungsten source, the erbium source and the ruthenium source is 1-2:1:60-100;

[0008] Furthermore, during calcination, the temperature is programmed to rise at a temperature gradient of 1 to 5°C / min;

[0009] Further, the ruthenium source includes, but is not limited to, one or more of ruthenium (III) chloride hydrate (RuCl3·xH2O), ruthenium acetate, and ruthenium acetylacetonate;

[0010] Further, the tungsten source includes but is not limited to one or more of tungsten chloride (WCl6), sodium metatungstate, and sodium tungstate dihydrate;

[0011] Further, the erbium source includes, but is not limited to, one or more of erbium nitrate hexahydrate (Er(NO3)3·6H2O), erbium chloride, and erbium bromide;

[0012] The W and Er doped RuO2 catalyst described in the present invention is prepared by the above method.

[0013] The W and Er doped RuO2 catalyst of the present invention can be used in the electrocatalytic water splitting oxygen release reaction under acidic conditions.

[0014] Compared with the prior art, the present invention has the following innovative features:

[0015] 1. Synthesize RuO2 catalyst with high performance, stable crystal structure and relatively low sample cost;

[0016] 2. The W and Er bimetallic doped RuO2 catalyst has a nanoparticle morphology with an ultra-small particle size (3-10 nm). This nanoparticle morphology can improve the electrochemical specific surface area and mass transfer efficiency of the obtained material to a certain extent ( Figure 2 and Figure 3 shown);

[0017] 3. In the obtained W and Er bimetallic doped RuO2 catalyst, the doping of W and Er regulates the electronic structure of RuO2 and significantly increases the density of active sites of the catalyst, thereby improving the intrinsic activity of the catalyst. Figure 4 shown);

[0018] 4. The obtained RuO2 catalyst is a new type of electrocatalytic water splitting catalyst, which exhibits excellent OER performance in 0.5M H2SO4 with a current density of 10mA cm -2 When the overpotential is only 140mV, the activity can be maintained for more than 130h. Figure 5 and Figure 6 shown). BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 : XRD spectrum of the W and Er bimetallic doped ruthenium oxide material obtained in Example 1;

[0020] Figure 2 : SEM image of the W and Er bimetallic doped ruthenium oxide material obtained in Example 1;

[0021] Figure 3 : TEM image of the W and Er bimetallic doped ruthenium oxide material obtained in Example 1;

[0022] Figure 4 : XPS image of the W and Er bimetallic doped ruthenium oxide material obtained in Example 1;

[0023] Figure 5 : Polarization curve of oxygen evolution of W and Er bimetallic doped ruthenium oxide material obtained in Example 1;

[0024] Figure 6 : Catalytic stability curve of the W and Er bimetallic doped ruthenium oxide material obtained in Example 1. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with the accompanying drawings and embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0026] Embodiment 1:

[0027] 145 mg of ruthenium (III) chloride hydrate, 7.9 mg of tungsten chloride, 4.6 mg of erbium nitrate hexahydrate and 20 mL of deionized water were mixed to form solution B; 29.2 mg of ethylenediaminetetraacetic acid and 19.2 mg of citric acid were mixed with 20 mL of deionized water, and the pH was adjusted to 9 with ammonia water to form solution A. Solution B was added dropwise to solution A, and mixed evenly with a magnetic stirrer to obtain solution C. Solution C was transferred to a reactor and subjected to a hydrothermal reaction at 80°C for 12 hours. The obtained reaction solution was centrifuged to obtain a black precipitate, which was then dried at 60°C to obtain a black solid precursor. Finally, the solid precursor was loaded into a corundum boat and transferred to a muffle furnace for calcination at a gradient temperature of 300°C (4h) and 400°C (2h) in the order of 300°C (4h) and 400°C (2h) (heating rate of 5°C / min) to obtain W, Er bimetallic doped ruthenium oxide W-Er-RuO2. The molar ratio of the tungsten source, erbium source and ruthenium source was 2:1:70, and the product mass was 55 mg.

[0028] Some structural characterizations were carried out on the materials prepared by the above method. Figure 1 The XRD spectra of the obtained materials are consistent with the rutile structure of RuO2 (PDF: #01-071-4825), indicating that the addition of W / Er ​​into the RuO2 lattice does not change the tetragonal structure of RuO2. Figure 2 The SEM spectrum of the obtained material shows that the morphology of the material is a nanoparticle form with a small size (3 to 10 nm). Figure 3 The high-resolution transmission electron microscopy (HRTEM) images show that the W-Er-RuO2 nanoparticles are composed of RuO2 mainly with (110) surface; Figure 4 The X-ray photoelectron spectroscopy (XPS) diagram of the obtained material before and after OER. The XPS analysis of its composition and chemical state shows the changes in the valence states of different elements in the catalyst. The XPS results after OER show that W transfers electrons to Ru and Er through O, controlling the valence state of the Ru element, allowing Ru to continuously obtain electrons to stabilize Ru 4+ The existence of the state indicates that the doping of W and Er regulates the electronic structure of metal Ru in the catalyst.

[0029] The material prepared by the above method was tested for its electrocatalytic oxygen evolution properties in a standard three-electrode electrolytic cell; the working electrode in the electrolytic cell was W, Er bimetallic doped ruthenium oxide W-Er-RuO2, the reference electrode was a saturated calomel electrode, and the counter electrode was a platinum wire.

[0030] Electrocatalytic oxygen evolution performance;

[0031] Catalytic activity test: Figure 5As shown in Figure 2, under the condition of 0.5M H2SO4, when the overpotential is 140mV, the current density of the material reaches 10mA / cm -2 .

[0032] Catalytic stability test: Figure 6 As shown, under 0.5M H2SO4 conditions, after 130h of operation, its catalytic performance has almost no attenuation.

[0033] Embodiment 2:

[0034] It is basically the same as Example 1, except that it should be noted that the molar ratio of the tungsten source, erbium source and ruthenium source is 1.1:1:80.

[0035] Under the condition of 0.5M H2SO4, when the overpotential is 212mV, the current density of the material reaches 10mA / cm -2 , and after 50h of operation, its catalytic performance had almost no attenuation, and the product mass was 50.5mg.

[0036] Embodiment 3:

[0037] It is basically the same as Example 1, except that it should be noted that the molar ratio of the tungsten source, erbium source and ruthenium source is 1.2:1:100.

[0038] Under the condition of 0.5M H2SO4, when the overpotential is 199mV, the current density of the material reaches 10mA / cm -2 , and after 60h of operation, its catalytic performance had almost no attenuation, and the product mass was 47.3mg.

[0039] Embodiment 4:

[0040] The process is basically the same as Example 1, except that the pH of solution A is 7.

[0041] Under the condition of 0.5M H2SO4, when the overpotential is 230mV, the current density of the material reaches 10mA / cm -2 , and after 40h of operation, its catalytic performance had almost no attenuation, and the product mass was 42.2mg.

[0042] Embodiment 5:

[0043] The process is basically the same as Example 1, except that the pH of solution A is 8.

[0044] Under the condition of 0.5M H2SO4, when the overpotential is 200mV, the current density of the material reaches 10mA / cm -2 , and after 60h of operation, its catalytic performance had almost no attenuation, and the product mass was 53.1mg.

[0045] Embodiment 6:

[0046] The process is basically the same as Example 1, except that the pH of solution A is 10.

[0047] Under the condition of 0.5M H2SO4, when the overpotential is 185mV, the current density of the material reaches 10mA / cm -2 , and after 50h of operation, its catalytic performance had almost no attenuation, and the product mass was 55.7mg.

[0048] Embodiment 7:

[0049] It is basically the same as Example 1, except that it should be noted that the hydrothermal reaction temperature of W-Er-RuO2 is 70°C.

[0050] Under the condition of 0.5M H2SO4, when the overpotential is 200mV, the current density of the material reaches 10mA / cm -2 , and after 90h of operation, its catalytic performance had almost no attenuation, and the product mass was 40.1mg.

[0051] Embodiment 8:

[0052] It is basically the same as Example 1, except that it should be noted that the hydrothermal reaction temperature of W-Er-RuO2 is 90°C.

[0053] Under the condition of 0.5M H2SO4, when the overpotential is 190mV, the current density of the material reaches 10mA / cm -2 , and after 100h of operation, its catalytic performance had almost no attenuation, and the product mass was 53mg.

[0054] Embodiment 9:

[0055] It is basically the same as Example 1, except that it should be noted that the hydrothermal reaction temperature of W-Er-RuO2 is 100°C.

[0056] Under the condition of 0.5M H2SO4, when the overpotential is 195mV, the current density of the material reaches 10mA / cm -2 , and after 95h of operation, its catalytic performance had almost no attenuation, and the product mass was 50mg.

[0057] Embodiment 10:

[0058] It is basically the same as Example 1, except that it should be noted that the calcination temperature of W-Er-RuO2 is 300°C (4h) and gradually increased to 600°C (2h).

[0059] Under the condition of 0.5M H2SO4, when the overpotential is 220mV, the current density of the material reaches 10mA / cm-2 , and after 20h of operation, its catalytic performance had almost no attenuation, and the product mass was 44.6mg.

[0060] Embodiment 11:

[0061] It is basically the same as Example 1, except that it should be noted that the calcination temperature of W-Er-RuO2 is gradually increased from 300°C (4h) to 900°C (2h).

[0062] Under the condition of 0.5M H2SO4, when the overpotential is 250mV, the current density of the material reaches 10mA / cm -2 , and after 15h of operation, its catalytic performance had almost no attenuation, and the product mass was 52mg.

[0063] Embodiment 12:

[0064] It is basically the same as Example 1, except that it should be noted that the gradient heating rate during the calcination of W-Er-RuO2 is 1°C / min.

[0065] Under the condition of 0.5M H2SO4, when the overpotential is 220mV, the current density of the material reaches 10mA / cm -2 , and after 50h of operation, its catalytic performance has almost no attenuation, and the product mass is 40mg.

[0066] Embodiment 13:

[0067] It is basically the same as Example 1, except that it should be noted that the gradient heating rate during the calcination of W-Er-RuO2 is 3°C / min.

[0068] Under the condition of 0.5M H2SO4, when the overpotential is 223mV, the current density of the material reaches 10mA / cm -2 , and after 63h of operation, its catalytic performance had almost no attenuation, and the product mass was 53.4mg.

[0069] Embodiment 14:

[0070] It is basically the same as Example 1, except that the ruthenium source is replaced with ruthenium acetate.

[0071] Under the condition of 0.5M H2SO4, when the overpotential is 189mV, the current density of the material reaches 10mA / cm -2 , and after 100h of operation, its catalytic performance had almost no attenuation, and the product mass was 56mg.

[0072] Embodiment 15:

[0073] It is basically the same as Example 1, except that the ruthenium source is replaced with ruthenium acetylacetonate.

[0074] Under the condition of 0.5M H2SO4, when the overpotential is 190mV, the current density of the material reaches 10mA / cm -2 , and after 90h of operation, its catalytic performance had almost no attenuation, and the product mass was 53mg.

[0075] Embodiment 16:

[0076] The process is basically the same as Example 1, except that the tungsten source is replaced with sodium metatungstate.

[0077] Under the condition of 0.5M H2SO4, when the overpotential is 190mV, the current density of the material reaches 10mA / cm -2 , and after 90h of operation, its catalytic performance had almost no attenuation, and the product mass was 44mg.

[0078] Embodiment 17:

[0079] The process is basically the same as Example 1, except that the tungsten source is replaced with sodium tungstate dihydrate.

[0080] Under the condition of 0.5M H2SO4, when the overpotential is 200mV, the current density of the material reaches 10mA / cm -2 , and after 80h of operation, its catalytic performance had almost no attenuation, and the product mass was 47.2mg.

[0081] Embodiment 18:

[0082] It is basically the same as Example 1, except that the erbium source is replaced with erbium chloride.

[0083] Under the condition of 0.5M H2SO4, when the overpotential is 198mV, the current density of the material reaches 10mA / cm -2 , and after 85h of operation, its catalytic performance had almost no attenuation, and the product mass was 48.1mg.

[0084] Embodiment 19:

[0085] It is basically the same as Example 1, except that the erbium source is replaced with erbium bromide.

[0086] Under the condition of 0.5M H2SO4, when the overpotential is 220mV, the current density of the material reaches 10mA / cm -2 , and after 70h of operation, its catalytic performance has almost no attenuation, and the product mass is 52mg.

[0087] The above-mentioned implementation modes are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes, substitutions and improvements that can be easily thought of by technicians familiar with the technical field within the spirit and principles of the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for preparing a W and Er doped RuO2 catalyst, characterized in that: First, citric acid and ethylenediaminetetraacetic acid are added to deionized water, and the pH value of the solution is adjusted to 7-10 to prepare solution A; ruthenium source, erbium source and tungsten source are added to deionized water, stirred until uniformly dissolved to form solution B; solution A and solution B are mixed uniformly, added to a reactor and hydrothermally reacted at 70-100° C. for 10-15 hours; the obtained reaction solution is centrifuged to obtain a black precipitate, and then dried at 50-70° C. to obtain a black solid; finally, in an air atmosphere, calcined at 280-320° C. for 3-5 hours and at 380-900° C. for 1.5-3.0 hours, respectively, to obtain the W and Er doped RuO2 catalyst.

2. The method for preparing a W and Er doped RuO2 catalyst according to claim 1, characterized in that: The molar ratio of the tungsten source, the erbium source and the ruthenium source is 1-2:1:60-100.

3. The method for preparing a W and Er doped RuO2 catalyst as claimed in claim 1, characterized in that: During calcination, the temperature is programmed to rise at a temperature gradient of 1 to 5°C / min.

4. The method for preparing a W and Er doped RuO2 catalyst as claimed in claim 1, characterized in that: The ruthenium source is one or more of ruthenium (III) chloride hydrate, ruthenium acetate, and ruthenium acetylacetonate.

5. The method for preparing a W and Er doped RuO2 catalyst as claimed in claim 1, characterized in that: The tungsten source is one or more of tungsten chloride, sodium metatungstate, and sodium tungstate dihydrate.

6. The method for preparing a W and Er doped RuO2 catalyst as claimed in claim 1, characterized in that: The erbium source is one or more of erbium nitrate hexahydrate, erbium chloride, and erbium bromide.

7. A W and Er doped RuO2 catalyst, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the W and Er doped RuO2 catalyst according to claim 7 in electrocatalytic water splitting oxygen release reaction under acidic conditions.